Financial Planning and Investment Feasibility Analysis of the Warehousing Startup Company Secure Stash - Helmy Hendra Kusuma; Rhian Indradewa; Edi Hamdi; Muhammad Dhafi Iskandar (Universitas Nusantara PGRI Kediri, 2025)
This study examines the financial planning and investment feasibility of Secure Stash, a technology-based startup operating in the warehousing service industry. Amid the rapid digital transformation and the expansion of e-commerce, modern warehousing supported by digital and Internet of Things (IoT) systems has become a critical component of efficient logistics and supply chain management. This research contributes by integrating a technology-driven business context with a comprehensive financial feasibility assessment, providing empirical insight into how digital warehousing startups can achieve sustainable financial performance. The study employs a descriptive quantitative approach using internal financial planning data of Secure Stash, including projected revenues, operating costs, capital structure, and investment requirements. Investment feasibility is evaluated using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Weighted Average Cost of Capital (WACC). These methods allow for a systematic assessment of both profitability and capital efficiency under startup conditions. The results indicate that the Secure Stash project is financially viable, with a positive NPV, an IRR exceeding the WACC, and a payback period within a reasonable timeframe for logistics startups. This study highlights the importance of integrating digital technology considerations with sound financial planning to support informed investment decisions and long-term business sustainability in the warehousing service sector.